University-led Intellectual Property Commercialization: Cases of Malaysian Universities - SM. , Sharif; A. , Isa; A.Y.M. , Noor; A.Z., Samsudin; M.A.M , Nizah; M.S.A. , Azzis (International Journal of Psychosocial Rehabilitation, 2020)
Universities are the centre place of innovation, which has recently given greater im-portance due to its potentially sustainable innovation creation. The process through which innovation comes from the universities to industries, which is also called Intellectual Property (IP) commercialization process, tends to be affected by various factors and contexts. The broad objective of this study to explain the current status of the IP commercialization in Malaysian universities. This study is undertaken to explain the intensity of IP commercialization, its processes and factors affecting IP commercialization in selected Malaysian universities. University Sains Malaysia (USM) and Universiti Teknikal Malaysia Melaka (UTeM) are the two universities selected at convenience and three layers of officials; top, middle and low levels, at the research offices of these universities were interviewed using semistructured depth interview protocol. The findings indicate that intensity of IP commercialization depends on experience, industry linkage, properly planned area of re-searches and active researchers researching different research institutes. This research will contribute to the existing understating of the IP commercialization in the Malaysian context, along with necessary measures to be taken at the policy, industry and university levels to foster innovation for socio-economic development of the country.